Risk Factors for Prolonged Postoperative Opioid Use After Spine Surgery: A Review of Dispensation Trends From a State-run Prescription Monitoring Program. Issue 1 (1st January 2019) - Rosenthal, Brett D.; Suleiman, Linda I.; Kannan, Abhishek; Edelstein, Adam I.; Hsu, Wellington K.; Patel, Alpesh A.
Abstract : Introduction: Opioid abuse and dependence have a detrimental effect on elective orthopaedic surgeries, yet pain control is an important predictor of postoperative satisfaction. We aimed at better defining risk factors for prolonged postoperative opioid requirements and risk factors for patients requiring higher doses of opioids after spine surgery. Methods: The Illinois Prescription Monitoring Program was queried to analyze opioid dispensation patterns at 3 and 6 months postoperatively for adult patients who had spine surgery at a tertiary care hospital by a single surgeon over a 5-year period. Patients were divided into three groups: group 1 patients had opioid dispensed to them 3 and 6 months preoperatively, group 2 patients had opioid dispensed to them only at 3 months preoperatively, and group 3 patients did not have preoperative opioid prescriptions. Demographic characteristics, psychiatric history, smoking status, alcohol use, body mass index, surgical region, and presence of multiple prescribers were abstracted. Statistical analysis included multivariate modified Poisson regression, linear regression, and chi-squared testing when appropriate. Results: Patients in group 1 were at significantly increased risk of continued opioid usage than those in group 2 (relative risk, 3.934; 95% confidence interval, 1.691 to 9.150; P = 0.0015) and those in group 3 (relative risk, 4.004; 95% confidence interval, 1.712 to 9.365; P = 0.0014) at 6 months postoperatively. Group 1 patients also had larger quantities of opioid dispensed to them relative to patients in group 2 or group 3 ( P < 0.0001) at 6 months postoperatively. Discussion: Use of opioid medications at 6 months preoperatively is a risk factor for continued usage and at higher doses 6 months postoperatively. Level of Evidence: Level III: retrospective cohort study